Excel® VBA : 24-Hour Trainer - Urtis, Tom (Wrox, 2011)
This unique book-and-DVD package helps even non-programmers extend Excel with VBA Virtually every manual task in Excel can be automated with VBA, which increases your productivity and saves enormous amounts of time. This unique book-and-DVD package prepares you to get more out of Excel by using Visual Basic for Applications (VBA) to automate many routine or labor-intensive Excel tasks. Microsoft Excel MVP and author Tom Urtis walks through a series of lessons and illustrations, while the accompanying DVD provides demos and screencasts to complement each lesson. Introduces you to programming with Visual Basic for Applications (VBA), macro composition, and the programming environment Explains events programming, embedded controls, user forms, message boxes, input boxes, looping, and more Shows you how to control other Office applications from Excel, such as Word, Outlook, Access, and PowerPoint Includes enhanced coverage of each lesson on the DVD, which also offers detailed examples Provides ideas for applying VBA to everyday tasks in a way that's both practical and fun Use this book-and-DVD package to get the total learning experience of VBA for Excel!